Geographical Sociology : Theoretical Foundations and Methodological Applications in the Sociology of Location - Porter, Jeremy R. (Dordrecht : Springer Netherlands, 2012., 2017)
Part I: The Sociology of Location: Theoretical Foundations. Part II: Spatial Context in Social Research: Methodological Applications.